Long-term effects of on-the-job skills (mis)match on employee wellbeing and employability: a 7-wave longitudinal study - Koopmans, Linda; van den Tooren, Marieke; Preenen, Paul (Frontiers in Psychology, 2025)
On-the-job skills match, in which employee knowledge and proficiencies (skills) are well-matched with the needs of the job, is often considered more beneficial, both for employees as well as for organizations and society, than a mismatch. A mismatch can be underqualification (when the skill level is below that which is required in the job) and overqualification (when someone has too many skills for the job they are doing). In this paper, we examined dynamics in employees’ on-the-job skills (mis)match over time, as well as the impact of these (mis)matches on employee wellbeing and employability several years later. To this end, we used 7-wave longitudinal data (2015–2021) from TNO’s Dutch Cohort Study on Sustainable Employability (CODI). The sample consisted of 7,831 Dutch employees. Descriptive data showed that about one-third (36.5%) of employees consistently reported a skills match (from T1 through T7) and 50% reported at least one change in skills (mis)match between T1 and T7 (e.g., going from underqualification to a match, despite staying in the same job with the same employer). About one in eight (12.2%) consistently reported overqualification and a small proportion of employees (0.4%) consistently reported underqualification. Predictive analyses showed that prolonged on-the-job skills match (T1–T4) affected employees’ burnout complaints, job satisfaction, labor market position and employment status 1–3 years later. Further, it was shown that prolonged skills mismatches (underqualification and overqualification) affected employees’ general health, work engagement, job satisfaction, labor market position, work ability en employment status 1–3 years later. Also, a relation was found between overqualification and burnout complaints. Main findings and their implications are discussed and recommendations for reducing on-the-job skills mismatches are made.